Design of a Broadband Microwave Amplifier Using Fuzzy Logic Performance Data Sheets with a Artificial Immune System - Cengiz, Yavuz; Yucel, Firat; Gunes, Filiz (ELECTROMAGNETICS ACAD, 2009)
Optimization is one of the fundamental processes frequently encountered in the engineering problems and is highly nonlinear in terms of the descriptive parameters of the system. In this work, the fuzzy logic performance data sheets of the transistor axe employed to determine the feasible design target space in the optimization of a microwave amplifier. The potential gain characteristics with the associated source Z(S)(omega) and load Z(L)(omega) terminations functions axe utilized combined with the artificial immune data processing in the design of the microwave amplifiers. A typical example is given and its resulted performance ingredients are compared with the design targets.
Keywords: Engineering; Physics